To solve the system of equations
- \(3x - 4y = -4\)
- \(x + 3y = -10\)
using the elimination method, we will manipulate the equations to eliminate one variable.
First, let's multiply the second equation by 3 so that the coefficients of \(x\) match:
\[ 3(x + 3y) = 3(-10) \] This gives us:
\[ 3x + 9y = -30 \]
Now we have the following two equations:
- \(3x - 4y = -4\)
- \(3x + 9y = -30\)
Next, we will subtract the first equation from the second equation to eliminate \(3x\):
\[ (3x + 9y) - (3x - 4y) = -30 - (-4) \]
This simplifies to:
\[ 9y + 4y = -30 + 4 \] \[ 13y = -26 \]
Now, divide both sides by 13:
\[ y = -2 \]
Now that we have the value of \(y\), we can substitute it back into one of the original equations to find \(x\). We'll use the second equation:
\[ x + 3(-2) = -10 \] \[ x - 6 = -10 \] \[ x = -10 + 6 \] \[ x = -4 \]
So the solution to the system of equations is:
\[ (x, y) = (-4, -2) \]
Thus, the answer is:
\[ \boxed{(-4, -2)} \]